MANAGEMENT AND AUDITORS OF AUTOMATIC DATA PROCESSING (PAD) IN THE BUSINESS ENVIRONMENT - Rivera León, Félix Armando (2015)
In order to set realistic goals and carry out its functions effectively, the auditors of automatic data processing (EDP), should know what they expect their companies. Possess a clear understanding of the objectives of the administration. This booklet expresses these issues and describes some responsibilities that must exist between the EDP auditor and management in enterprises.